Finding continue iteration cycles.

=> equivalent to solving

A(z)

F(z+1) = A(F(z))

G(s,z) = F(F^-1(z) + s)

Z=(a,b) = a + b i

Jordan curve C(a,b) given by D(a,b) = 0.

H(z) = G ' (0,z) ds - 1.

Arg H(z) = Tan C ' (a,b)

And H(z) =\= 0 on C(a,b).

Regards

Tommy1729

=> equivalent to solving

A(z)

F(z+1) = A(F(z))

G(s,z) = F(F^-1(z) + s)

Z=(a,b) = a + b i

Jordan curve C(a,b) given by D(a,b) = 0.

H(z) = G ' (0,z) ds - 1.

Arg H(z) = Tan C ' (a,b)

And H(z) =\= 0 on C(a,b).

Regards

Tommy1729